e-Generation of Tests and e-Class Record in a Flexible Learning Environment - Patacsil, Frederick Flores (Universitas Negeri Makassar, 2024)
As assessment is an integral part of student learning, schoolteachers need to create appropriate assessments, through the use of the Table of Specifications, to get accurate feedback from the students. Recording of student performance is also important to provide basis and transparency to student grades. However, these activities are laborious when performed. This study aims to development and validate a web application that covers the electronic generation of tests with Table of Specification (TOS) and the recording of student performances in an electronic class record (grade book). User requirements were captured through interviews and documentary analysis. The application was developed using the Agile Scrum Framework and was tested for usability using the System Usability Scale (SUS). The developed system proved to be usable with a general SUS score of 81.25 which is interpreted as usable and conforms to the given requirements. The results indicates that the developed system is very useful to the teachers specially during this pandemic period were flexible learning is utilized for teaching and learning.